2019
DOI: 10.1002/prca.201800104
|View full text |Cite
|
Sign up to set email alerts
|

Stearate‐Induced Apoptosis in Human Pancreatic β‐Cells is Associated with Changes in Membrane Protein Expression and These Changes are Inhibited by Oleate

Abstract: Purpose: Lipotoxicity is implicated in type 2 diabetes pathogenesis. Its molecular mechanisms are not completely understood. The aim of this study is to identify new suspect proteins involved in pancreatic ␤-cell death induction by saturated fatty acids and its inhibition by unsaturated fatty acids. Experimental design: Employing 2DE analysis and subsequent western blot confirmation, the differences in membrane/membrane-associated protein expression in human ␤-cell line NES2Y are assessed during cell death ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Other molecules/events speculated to play a role in the mechanisms of FA-induced β-cell apoptosis include activation of transcription factor NF-κB (nuclear factor kappa B) [5,104,114,245,246], GPR120 [139], FAT/CD36 (fatty acid translocase/cluster of differentiation 36) [247], cathepsin D [208] and calpain-10 [248]; degradation of carboxypeptidase E [39]; cellular localization of annexin A2 and A4, reticulocalbin-2 and 14-3-3γ [249]; expression of Nck1 [250] and JunB downregulation [103].…”
Section: Other Mechanisms Involvedmentioning
confidence: 99%
“…Other molecules/events speculated to play a role in the mechanisms of FA-induced β-cell apoptosis include activation of transcription factor NF-κB (nuclear factor kappa B) [5,104,114,245,246], GPR120 [139], FAT/CD36 (fatty acid translocase/cluster of differentiation 36) [247], cathepsin D [208] and calpain-10 [248]; degradation of carboxypeptidase E [39]; cellular localization of annexin A2 and A4, reticulocalbin-2 and 14-3-3γ [249]; expression of Nck1 [250] and JunB downregulation [103].…”
Section: Other Mechanisms Involvedmentioning
confidence: 99%
“…Meanwhile, a long-term high level of stearic acid exhibited a stronger destructive effect on β cells than that of palmitic acid [ 5 , 8 ]. Although endoplasmic reticulum (ER) stress [ 5 , 9 ] and apoptosis [ 8 , 10 ] are accepted as major contributors to stearic acid-induced β cell dysfunction, the molecular mechanisms involved in this remain largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we investigated whether stearate induced apoptosis like palmitate, as reported previously 12,14,16 . A ow cytometry analysis of Annexin V-positive cells showed that stearate increased apoptosis of OVCAR5 cells dose-dependently (Figs.…”
Section: Stearate Induces Apoptosis and Dna Damage In Ovarian Cancer ...mentioning
confidence: 77%